Dissembling Orthodoxy in the Age of the Enlightenment: Frederick the Great and his Confession of Faith*. (6th January 2016) - Kloes, Andrew
Abstract : The name of Friedrich II and his nearly half-century reign from 1740 to 1786 are virtually synonymous with the advent and advance of the Enlightenment in Prussia. In his famous 1784 answer to the question posed by the Berlinische Monatsschrift, "What is enlightenment?" Immanuel Kant asserted that enlightenment could be partially conceptualized as a temporal epoch, one whose salient characteristics, especially in regards to religion, were manifested in the personal opinions and public policies of his royal Prussian sovereign. "We do not live in an enlightened age, but in an age of enlightenment – the century of Friedrich." In a similar spirit, a generation after Kant wrote, Friedrich Schleiermacher delivered a paean to Friedrich II's memory in a January 24, 1817 address to the Prussian Academy of Sciences on what would have been Friedrich II's one-hundred-and-fifth birthday. Schleiermacher heralded Friedrich II as "a friend of the muses, " who doubtlessly conversed with Plato in the afterlife, the legacy of whose domestic initiatives had been to transform Prussia into a more cultured society, while his "heroic" and "glorious" victories secured for the Prussian Army its vaunted reputation for military prowess. As the 29-year-old king himself wrote in a February 24, 1741 battlefield letter from the frontlines of the First Silesian War, "I love war for its glory, but if I were not a ruler, I would be nothing but a philosopher."